2016
DOI: 10.5604/18972764.1229622
|View full text |Cite
|
Sign up to set email alerts
|

The properties of experimental silicones reinforced with silica fillers for dentistry

Abstract: Purpose: Silicone materials crosslinked during the hydrosilylation reaction are common in dental prosthetics and dentistry. These materials are characterized by a relatively very good properties. However, one of the fundamental problems associated with the use of such polymers is a low resistance to microbial colonization. Numerus fillers with antimicrobial potential have been used experimentally for a decade. Anyway point of concern in this type of work is the use of commercially available materials as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Silica (SiO 2 ) has been shown to produce significant improvements in both tensile strength and hardness when incorporated at 15% by weight [ 19 ]. Zayed et al found significant improvement at 3% by weight for tensile strength (0.84 MPa), tear strength (26.58 N/mm) and hardness (1.88 shore A).…”
Section: Discussionmentioning
confidence: 99%
“…Silica (SiO 2 ) has been shown to produce significant improvements in both tensile strength and hardness when incorporated at 15% by weight [ 19 ]. Zayed et al found significant improvement at 3% by weight for tensile strength (0.84 MPa), tear strength (26.58 N/mm) and hardness (1.88 shore A).…”
Section: Discussionmentioning
confidence: 99%
“…Adding filler particles to the maxillofacial silicone can benefit in increasing mechanical properties. According to the meta-analysis study, adding filler increases tensile strength, tear strength, hardness, and elongation at break, but in some groups, the nanoparticles give more desirable properties compared to the microparticle groups [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Very high and still growing requirements for engineering materials makes it necessary to find much better and advanced solutions able to meet the new demands [1][2][3]. This trend can be observed in both metals, polymers, ceramics and composites [4,5].…”
Section: Introductionmentioning
confidence: 99%